A new organoleptic testing method for evaluating halitosis - Kim, Dae-Jung; Lee, Jeong-Yun; Kho, Hong-Seop; Chung, Jin-Woo; Park, Hee-Kyung; Kim, Young-Ku (Journal of periodontology (1970), 2009)
Halitosis is a common condition in the adult population. The organoleptic method has been used widely in the clinical field for the diagnosis of halitosis because of its simplicity; however, this method has limitations as a result of its lack of objectivity and reproducibility. We developed a new method of organoleptic testing using a gastight syringe to overcome these limitations. The purpose of this study was to investigate the clinical usefulness of this new method by analyzing the correlations between the organoleptic score measured by it and data from the portable sulfide monitor and gas chromatography in the same subjects. Fifty-two subjects (20 males and 32 females; mean age, 35.6 +/- 12.8) who visited the Halitosis Clinic at Seoul National University Dental Hospital, were recruited. We recorded the organoleptic score and measured the concentration of volatile sulfur compounds (VSCs) using a portable sulfide monitor and gas chromatography. The organoleptic test was performed in a standardized way using a gastight syringe and a paper cup connected to a plastic straw. The organoleptic score by the new method showed a significant positive correlation with the total VSC concentrations that were measured by gas chromatography (r = 0.790; P <0.01) and with the portable sulfide monitor (r = 0.822; P <0.01). There were significant positive correlations between the organoleptic score obtained by the new method and the concentration of H(2)S (r = 0.776; P <0.01), CH(3)SH (r = 0.715; P <0.01), and (CH(3))(2)S (r = 0.674; P <0.01) measured by gas chromatography. The new organoleptic test is a valuable tool for measuring halitosis in the clinical field.